Más allá de las aulas: relación entre experiencias adversas infantiles, satisfacción familiar y salud mental en estudiantes universitarios - Mieles, Ismael (2024)
This study adopts a descriptive correlational design to examine the interrelationship between levels of anxiety and depression, adverse childhood experiences, and family satisfaction in 304 university students from different programs. The instruments IDER, STAI, ACE and the Family Satisfaction Scale were used. Normal levels of depression and family satisfaction were reported; however, 35% of the participants presented elevated scores of state depression and 29% of trait depression. High scores in state anxiety (69,9%) and trait anxiety (74,2%) were reported, and with respect to adverse childhood situations, 37,8% of the participants reported experiencing more than one of the listed situations. A relationship was identified between these emotional states, adverse childhood experiences and the influence of socio-economic status on family satisfaction. These findings suggest the importance of addressing mental health in the university setting.